Rancang bangun sistem pengontrol temperatur menggunakan mikrokontroller ATSAM3X8E pada peralatan ultrasonic assisted extraction (UEA) - Siti Hastin Nur Indarwati; Isnain Gunadi; Suryono Suryono (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
In this research, design of temperature control system has been made for Ultrasonic Assisted Extraction (UAE) equipment. The system consisted of elemen pemanas, temperature, sensor such as Resistance Temperature Detector (RTD) sensor, relay, microcontroller and computer interface. Microcontroller that used in this system is ATSAM3X8E microcontroller that connected with computer interface as the temperature data viewer that is using Borland Delphi 7. Temperature controller could be built by RTD sensor through computer interface so it could save and show the data in MySQL database. This system ca be applied as temperature controller system for extraction equipment. From this research’s result showed system that has been built can measure and control temperature using RTD sensor with the error’s value in measurement is 0,04oC. From the controlling system testing’s result with given set point is 35oC can be known that tis controlling system has delay until it started which is for 6 minutes with the control stability’s condition 97,09% and error value 2,91%.Keywords: temperature, controller, RTD sensors, database, MySQL